Becoming an artist: exploring the motivations of undergraduate students at a regional Australian University. Issue 6 (3rd June 2017) - Daniel, Ryan; Johnstone, Robert
Abstract : Despite the well-documented challenges that artists face in developing and sustaining a viable career, there is ongoing interest and enrolment in higher education programmes in the creative and performing arts. At the same time, extant research demonstrates that a higher education degree does not necessarily lead to enhanced career success for graduates of these programmes. Hence, this paper explores survey data from 120 creative and performing arts students at a regional Australian higher education institution, in terms of their motivation to study at this level and to pursue a career as an artist. The findings reveal various insights into the factors that motivate this group of students, as well as issues of wider relevance to providers of higher education programmes in the creative and performing arts.